Color Stability of Bulk-Fill Flowable Resin Composites After Artificial Aging - Franciele Floriani; Carlos A. Jurado; Nikkita Madhu; Mark A. Lackey; Francisco X. Azpiazu-Flores; Guilherme Carpena Lopes (MDPI AG, 2024)
Background: This study aimed to evaluate the color stability of bulk-fill flowable resin composites with 2 difference shades at baseline and after artificial aging. Methods: Disk-shaped specimens (Ø10 × 4 mm) were fabricated from three bulk-fill flowable resin resin composites (Filtek Bulk-Fill Flow, Venus Bulk-Fill Flow, and Estelite Bulk-Fill Flow). The specimens in each bulk-fill resin composite group were divided into two subgroups (n = 10 per subgroup) with two different shades, A1 (N = 30) and A3 (N = 30), and were polymerized with light curing (800 mW/cm2/Valo LED Unit, Ultradent) and polished. The color difference between bulk-fill resin composites was evaluated at baseline and after artificial aging using a spectrophotometer (CM-700d, Konica Minolta, Tokyo, Japan) under D65 illumination. Color coordinates were measured with CIEDE2000, and color differences (∆E00) and relative translucency parameter (RTP) values were calculated. Subsequently, the comparison of color changes (∆E00) before and after thermocycling was performed using the t-test for paired samples. Results: The bulk-fill flow resin composites evaluated in the present study were capable of mimicking important optical properties such as light transmission. All the resin composites provided acceptable color stability at baseline and after thermocycling when the color A1 was used. On the other hand, whenever the shade A3 was used, the Venus Bulk-Fill Flow demonstrated the best optical properties. There was no statistically significant difference when comparing baseline and after thermocycling in bulk-fill flowable resin composites (p > 0.05). After thermocycling, A1 bulk-fill flowable resin composites provided acceptable color stability, and all A3 bulk-fill flowable resin composites provided visible color change, except for the Venus Bulk-Fill Flow (∆E00 = 2.35). Conclusions: Estelite Bulk-Fill Flow displayed the best color stability (∆E00 = 2.22) between all the combinations evaluated.